On the Use of Permselectivity to Describe the Selective Transfer of Organic Acids in Electrodialysis - Robin Caveriviere; Sylvain Galier; Hélène Roux-de Balmann (Membranes, 2023)
The increasing number of investigations on the use of electrodialysis (ED) in bio-refinery requires a better understanding and tools to evaluate and describe the transfer of charged organic solutes. This study focuses, as an example, on the selective transfer of acetate, butyrate, and chloride (used as a reference), characterized by using permselectivity. It is shown that permselectivity between two anions does not depend on the total ion concentration, neither on the ion proportions, current intensity, or time nor on the presence of an additional compound. Therefore, it is demonstrated that permselectivity can be used to model the evolution of the stream composition during ED, even at high demineralization rates. Indeed, a very good agreement is found between experimental and calculated values. This study and the application of permselectivity as a tool, as developed in this paper, could be highly valuable for a wide range of applications in electrodialysis.